Association of age with perioperative morbidity among patients undergoing surgical management of minor burns - Knoedler, Samuel; Matar, Dany Y.; Knoedler, Leonard; Obed, Doha; Haug, Valentin; Gorski, Sabina M.; Kim, Bong-Sung; Kauke-Navarro, Martin; Kneser, Ulrich; Panayi, Adriana C.; Orgill, Dennis P.; Hundeshagen, Gabriel (Frontiers in Surgery, 2023)
Burn injuries are associated with significant morbidity, often necessitating surgical management. Older patients are more prone to burns and more vulnerable to complications following major burns. While the relationship between senescence and major burns has already been thoroughly investigated, the role of age in minor burns remains unclear. To better understand differences between elderly and younger patients with predominantly minor burns, we analyzed a multi-institutional database. We reviewed the 2008-2020 ACS-NSQIP database to identify patients who had suffered burns according to ICD coding and underwent initial burn surgery. We found 460 patients, of which 283 (62%) were male and 177 (38%) were female. The mean age of the study cohort was 46 ± 17 years, with nearly one-fourth (n=108; 23%) of all patients being aged ≥60 years. While the majority (n=293; 64%) suffered from third-degree burns, 22% (n=99) and 15% (n=68) were diagnosed with second-degree burns and unspecified burns, respectively. An average operation time of 46 minutes, a low mortality rate of 0.2% (n=1), a short mean length of hospital stay (1 day), and an equal distribution of in- and outpatient care (51%, n=234 and 49%, n=226, respectively) indicated that the vast majority of patients suffered from minor burns. Patients aged ≥60 years showed a significantly prolonged length of hospital stay (p<0.0001) and were significantly more prone to non-home discharge (p<0.0001). In univariate analysis, advanced age was found to be a predictor of surgical complications (p =0.001) and medical complications (p=0.0007). Elevated levels of blood urea nitrogen (p>0.0001), creatinine (p>0.0001), white blood cell count (p=0.02), partial thromboplastin time (p=0.004), and lower levels of albumin (p=0.0009) and hematocrit (p>0.0001) were identified as risk factors for the occurrence of any complication. Further, complications were more frequent among patients with lower body burns. In conclusion, patients ≥60 years undergoing surgery for predominantly minor burns experienced significantly more complications. Minor lower body burns correlated with worse outcomes and a higher incidence of adverse events. Decreased levels of serum albumin and hematocrit and elevated values of blood urea nitrogen, creatinine, white blood count, and partial thromboplastin time were identified as predictive risk factors for complications.